A Critical Discourse Analysis of Sara Mills on Popular Memes in Indonesia - Almanar, Muhammad Abduh (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2025)
This study aimed to analyze the elements within memes and critique the hidden messages that appeared on the internet and social media. Employing a critical discourse analysis method from Sara Mills' approach, the researcher examined two selected memes to be analyzed and reviewed. Key aspects of this analysis included power dynamics, identity, linguistic structure, intertextuality, and ideology of the memes. The result of the study revealed that the first meme highlighted a critique of technological advancements in the learning process. The first meme revealed that the students' misuse of AI (Artificial Intelligence) tools like ChatGPT led to increasing dependency on technology for the study. Academic integrity builds essential skills such as creativity, collaboration, and problem-solving that AI cannot replace. The need for balanced and proper technology use toward technology in education has become a social critique and stakeholder’s concern for technology integration in education. On the other side, academic pressure also fostered students to an over-reliance on technology. Furthermore, the researcher found that technological innovation significantly challenged academic integrity in learning. Besides, the following meme issues illustrated two different orientation practices for new students. Inappropriate academic practice during orientation day showed ideological gaps and psychological impacts on students, such as trauma, fear, and low self-esteem. Employing humor with an element of sarcasm and satire, a clear message aiming stakeholders in higher academics to stop inappropriate practices over the years.